2009
DOI: 10.1590/s1677-55382009000500008
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic radical prostatectomy: 10 years experience

Abstract: Purpose:The authors assess the morbidity, functional results and oncologic follow-up of a series of laparoscopic radical prostatectomies performed in over a 10-year period. Materials and Methods:The data on 780 laparoscopic radical prostatectomies performed between September 1997 and December 2007 were stored in a personal database. The following parameters are described and critically analyzed: operative time, blood transfusions, conversions, length of hospital stay, complications, functional results of sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
3
3
0
1
Order By: Relevance
“…Similarly to our results, Mirandolino et al ( 6 ) reported that the PSM average obtained in cases under LRP was from 11%-26%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly to our results, Mirandolino et al ( 6 ) reported that the PSM average obtained in cases under LRP was from 11%-26%.…”
Section: Discussionsupporting
confidence: 92%
“…In a series of 760 cases, Mirandolino et al ( 6 ) found that the percentage of PSM in LRP was similar to the studies using the open technique. The PSM average was from 11% to 26%.…”
Section: Introductionsupporting
confidence: 65%
“…Since the main goal of LRP is oncologic success, initial experience could be based on a PSM rate that should be 0%, but in practice 15% is considered acceptable. Our PSM rates were 20% in pT2 and 43.6% in pT3 with no statistical improvement with experience, were comparable to many previous reports ( 2 , 3 , 11 , 12 , 20 , 24 ), although it was higher than series with PSM rates between 7.2 and 13.9%, probable due to the higher proportion of pT3 in our series ( 22 , 25 ). Many studies also described a plateau in the PSM after 250 cases ( 3 , 7 , 23 ), while for others the plateau occurred after 100 cases ( 26 ).…”
Section: Discussionsupporting
confidence: 87%
“…). Following assessment, 68 articles, involving 708 032 patients across 71 LMICs, were included in the review ( Tables S1 and S2 , supporting information). Country‐specific patient numbers were reported in 60 studies but were absent from six and two provided total LMIC patient numbers only.…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes following cancer surgery were common topics, including breast, gastric, colorectal and prostate cancer, and hepatocellular carcinoma. Cardiac surgery, caesarean section and genitourinary fistula were also well represented in included articles, whereas clinical presentations included burn management, trauma, appendicitis, groin hernias and orthopaedic fracture management.…”
Section: Resultsmentioning
confidence: 99%